If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y/9-3=11
We move all terms to the left:
y/9-3-(11)=0
We add all the numbers together, and all the variables
y/9-14=0
We multiply all the terms by the denominator
y-14*9=0
We add all the numbers together, and all the variables
y-126=0
We move all terms containing y to the left, all other terms to the right
y=126
| 3x^2+2x-124=0 | | -2/3x-10=-2(1/3x+5) | | -2/3x-10=-21/3x-10 | | 30=-15+15z | | 7a+6a=6a+24 | | _-40=12x+8 | | 3y=y-8+2 | | 2x-7-2x=1 | | 3x+14=2x-3 | | 4a+1–a=19 | | 11-7=3y-4 | | y=6.2–3(2+5) | | 2x²-1=199 | | 4(x+5)=x+4 | | 19=h÷3-8 | | b+19.8=–9.2 | | 4/5x+5/5=-2/5 | | 4/5y-1=2/5y=4/15 | | x^+4x-9=x+1 | | 0.5x-0.25-0.2x=x-0.9 | | -11.4=u/8+1.4 | | -7.8=-1.4+x/4 | | (100+x)/2=94 | | 2(x/2-4=8 | | 8b^2+12b-6=0 | | 3x=4x-3x+37 | | -x-x=-2x | | -5x-3x=-2x | | -3x-x=-2x | | ?x12+43-85=246 | | 10^6x=100^2x+3 | | 5x-17=-×+7× |